Effects of Different Irrigation Solutions and Protocols on Mineral Content and Ultrastructure of Root Canal Dentine - Nogueira, Brenna Magdalena Lima; Pereira, Thais Isabele da Costa; Pedrinha, Victor Feliz; Rodrigues, PatrÃcia de Almeida (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to evaluate the effect of different irrigating solutions and irrigation protocols on the chemical and physical structure of root dentin. Materials and Methods: Thirty extracted single-rooted human teeth were selected and then distributed into the following treatment groups (n=10): G1, saline solution (0.9% NaCl); G2, 2.5% NaOCl + 17% EDTA + 2.5% NaOCl; G3, 2.5% NaOCl + 9% Etidronate (HEBP) + 2.5% NaOCl; G4, mixture of 5% NaOCl + 18% HEBP; G5, 2.5% NaOCl + 17% EDTA + 0.9% NaCl, and G6, 2.5% NaOCl + 9% HEBP + 0.9% NaCl. The ultrastructure of dentin was characterized through scanning electron microscopy (SEM) and energy dispersive x-ray spectrometry (EDS) determined the chemical composition in terms of the calcium (Ca), phosphorus (P), magnesium (Mg) and potassium (K) content and the Ca/P ratio; and the crystalline phase was analyzed by x-ray diffraction (XRD). A descriptive analysis was performed on the ultrastructure and the crystallography data of dentin. Data analysis included a chemical composition analysis of variance (one-way ANOVA) and a subsequent multiple comparison test (Tukey’s test). Results: Except for the control group, all groups showed morphological changes upon visualization with SEM. For EDS, G2 and G5 showed significant mineral loss and changes in the Ca/P ratio (P<0.05); the highest values of Ca and P were observed in G3, G4 and G6. Conclusion: All the irrigating solutions and irrigation protocols tested promoted changes in the morphology and physical and chemical composition of the dentin. However, no significant differences were observed crystallographically. Keywords: Chelating agent; Dentin; Root Canal Irrigant; Surface Properties